Pelvis, brain and evolution (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
We begin with a quote from Genesis, "With pain you will give birth to children" and we end by explaining it. The evolution of the pelvis in hominids was fundamental to allowing births of offspring with larger cranial volumes. Giving birth to an offspring with a highly developed brain through a pelvis deformed by bipedalism was a challenge that had to be solved for our species to thrive. We analyze the case of two famous pelvises, one from Australopithecus afarensis and the other from a Preneandertal, and then we study births in different hominids.
Keywords: hominid; pelvis; brain; evolution; childbirth.